Germination and seedling growth of holm oak (Quercus ilex L.): effects of provenance, temperature, and radicle pruning - Caliskan, Servet (IFOREST-BIOGEOSCIENCES AND FORESTRY, 2013)
This study tested acorn characteristics and the germination behavior of different provenances of Holm oak (Quercus ilex L.) and the effects of radicle clipping of germinated acorns on 1-0 year-old seedling morphology and their field performances. The results revealed that all acorn characteristics among different provenances were significant. Quercus ilex acorns germinated well at alternating temperatures of 20/10 degrees C compared to a constant 20 degrees C temperature. Radicle clipping of Q. ilex significantly increased the shoot height and root collar diameter. The average number of main roots resulting from radicle clipping was 2.8 times more than unclipped treatment. The results can contribute to nursery practices and artificial regeneration of this species.
The following values have no corresponding Zotero field: pub-location: DEPT PROD VEGETALE, VIA ATENEO LUCANO 10, POTENZA, 85100, ITALY publisher: SISEF-SOC ITALIANA SELVICOLTURA ECOL FORESTALE
Keywords: artificial regeneration; Holm oak; Quercus ilex; Radicle Pruning; seed germination; sowing

Artificial regeneration with Quercus ilex L. and Quercus suber L. by direct seeding and planting in southern Spain - González-Rodríguez, Victoria; Navarro-Cerrillo, Rafael M.; Villar, Rafael (Annals of Forest Science, 2011)
& Introduction The limited ability of Quercus species to regenerate naturally in Mediterranean forests has led to the development of various artificial regeneration methods; however, there is no general consensus as to what specific method is the best one for this purpose. & Material and methods In this work, we assessed morphology, growth and survival of two Quercus species (Quercus ilex ssp. ballota and Quercus suber) using two different methods of artificial regeneration (viz. direct seeding and planting) and two seedling ages (1-year-old seedlings and 3-year-old seedlings) in southern Spain. & Results and discussion The 1-year-old seedlings of both species were found to exhibit the highest survival percentages and direct-seeded plants intermediate survival values. For direct-seeded plants, seed mass was found to have a significantly positive effect on the establishment success in both species. No clear-cut trend in survival was detected in the 3- year-old seedlings. The survival of the 3-year-old Q. suber seedlings and the direct-seeded plants was similar, but not in Q. ilex, where the survival of the 3-year-old seedlings was the lowest. The latter result may have been a consequence of cultivation in smaller containers leading to root deformation and limiting plant access to water. Differences in survival could not be ascribed to morphological and growth variables or stomatal conductance. & Conclusion Based on the results, all three artificial regeneration methods can be similarly effective provided appropriate nursery cultivation conditions are used and seeds are protected against predators, the best choice in each case being dictated by the particular restoration goals.
Keywords: artificial regeneration; Nursery; oak; Seedling; sowing